Advances in Experimental Medicine and Biology
DOI: 10.1007/0-387-29540-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hypoxia Modulates Endothelium-Dependent Vasorelaxation Through Multiple Independent Mechanisms in Ovine Cranial Arteries

Abstract: Acclimatization to chronic hypoxia involves numerous compensatory changes in many tissues, including blood vessels. The present data demonstrate that in addition to well-documented changes in contractility, chronic hypoxia also produces important changes in the mechanisms mediating endothelium-dependent vasodilatation. At the level of the endothelium, hypoxia attenuates endothelial release of NO and this appears to be mediated through reductions in eNOS specific activity; chronic hypoxia has little effect on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Enhanced VEGF expression is known to induce increased permeability of endothelial cells leading to fenestrated vessels [25]. As we have shown previously [16], FL angiography allows the precise detection of fenestrated vasculature in vivo .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Enhanced VEGF expression is known to induce increased permeability of endothelial cells leading to fenestrated vessels [25]. As we have shown previously [16], FL angiography allows the precise detection of fenestrated vasculature in vivo .…”
Section: Discussionmentioning
confidence: 79%
“…The observed changes in vascular diameter were limited to retinal venules and retinal capillaries without affecting the retinal arterioles in Ndph y /- mice (Fig 3A–3C). This at first seems surprising since it is generally thought that chronic hypoxia induces a compensatory increase of either arteries in various systems including the carotid body [25, 26], or both arteries and veins in the retina [2729]. A potential explanation would be based on the manner the retinal vasculature develops during early life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their well-documented vasomotor roles, however, both of these factors also exert continuous and opposing trophic influences on adjacent smooth muscle. Given that hypoxia increases endothelin synthesis but decreases NO synthesis and release, both of these factors are important contributors to hypoxic vascular remodeling [66, 211]. …”
Section: Receptor Tyrosine Kinase-independent Vasotrophic Factorsmentioning
confidence: 99%
“…Regarding the NO/cGMP pathway, studies in the late 2000s indicated that chronic hypoxia depressed NO release via reduced eNOS specific activity without decreasing eNOS abundance [118]. In parallel, hypoxia also decreased soluble guanylate cyclase activity in fetal but not adult arteries without a change in mRNA abundance for guanylate cyclase [119]; hypoxia clearly affected some aspect of mRNA translation, suggesting the possible involvement of microRNAs.…”
Section: The 2000s: Calcium Cgmp Pkc and Fetal Cbfmentioning
confidence: 99%